Extension of the substrate spectrum by an amino acid substitution at residue 219 in the Citrobacter freundii cephalosporinase. - Tsukamoto, K (1990)
The cephalosporinase of Citrobacter freundii GN346 is a class C beta-lactamase, consisting of 361 amino acids and exhibiting the substrate profile of a typical cephalosporinase. On the conversion of a conserved glutamic acid at residue 219 to lysine, the substrate spectrum of the cephalosporinase was extended to oxyimino cephalosporins, aztreonam and carbenicillin, which are essentially undesirable substrates for the enzyme. Escherichia coli cells carrying the mutant gene showed higher resistance levels to cefuroxime, aztreonam, and carbenicillin, but a lower resistance level to cefoxitin, than cells carrying the wild gene. The kcat values of the purified mutant enzyme for ceftazidime, cefuroxime, and cefmenoxime were 77,100, and 300 times those of the wild enzyme, respectively. The relative Vmax values of the mutant enzyme for aztreonam and carbenicillin were determined to be 11 and 23 times those of the wild enzyme, respectively, but the value of the mutant enzyme for cefoxitin was only one-third that of the wild enzyme.